2012
DOI: 10.1103/physreve.85.016304
|View full text |Cite
|
Sign up to set email alerts
|

Generalized nonequilibrium capillary relations for two-phase flow through heterogeneous media

Abstract: For two-phase flow in porous media, the natural medium heterogeneity necessarily gives rise to capillary nonequilibrium effects. The relaxation to the equilibrium is a slow process which should be introduced in macroscopic flow models. Many nonequilibrium models are based on a phenomenological approach. At the same time there exists a rigorous mathematical way to develop the nonequilibrium equations. Its formalism, developed by Bourgeat and Panfilov [Computational Geosciences 2, 191 (1998)], is based on the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…Let us point out that the matrix-fracture source terms Q δ w , Q δ n of the system (1), given in an implicit form by (8), involve the function S δ m which is a solution of the local boundary value problem (16), which is coupled with the global problem (1)-(4) through its boundary condition. This feature of the system (1)- (8), (16) is captured by the concept introduced in [5]: the homogenized system of equations is said to be fully homogenized if it does not involve the unknown functions which are defined as the solutions of the coupled local problems. The global δ-problem (1)-(8), (16) is not fully homogenized in the said sense.…”
Section: Linearized Imbibition Equationmentioning
confidence: 99%
“…Let us point out that the matrix-fracture source terms Q δ w , Q δ n of the system (1), given in an implicit form by (8), involve the function S δ m which is a solution of the local boundary value problem (16), which is coupled with the global problem (1)-(4) through its boundary condition. This feature of the system (1)- (8), (16) is captured by the concept introduced in [5]: the homogenized system of equations is said to be fully homogenized if it does not involve the unknown functions which are defined as the solutions of the coupled local problems. The global δ-problem (1)-(8), (16) is not fully homogenized in the said sense.…”
Section: Linearized Imbibition Equationmentioning
confidence: 99%
“…As explained for example in [3,4,15], rock heterogeneities strongly influence the behavior of the flow, since a singular effect can be induced at the rock discontinuities. Therefore our purpose is to consider the capillarity only at the rock discontinuity, and to neglect it within the homogeneous domain where it plays a minor role.…”
Section: The Singular Limit As Capillarity Is Neglectedmentioning
confidence: 99%
“…The two-phase flow in double porosity media at local equilibrium is well studied; see, for example, [7][8][9]. It was shown that, in such systems, despite the local equilibrium, another nonequilibrium phenomenon appears on the macroscale, which is caused by the high delay in capillary redistribution of the fluids between blocks and fractures.…”
Section: Introductionmentioning
confidence: 99%